Polio, Eradikasi, dan Vaksinasi - Kenty Andika; Dika Amalia (Jurnal Medika Nusantara, 2024)
Poliomyelitis (polio) is a very dangerous infectious disease. The disease is caused by polio virus which comes from the genus Enterovirus and family Picorna viridae. Polio virus enters the body through the mouth, from water or food contaminated with feces of polio sufferers. Also also due to lack of personal and environmental hygiene. Polio has no cure, the only defense is immunization. The World Health Organization (WHO) stated that in 2018 there were around 20 million children in the world who did not get complete immunization, some even did not get immunized at all. Indonesia has implemented a polio eradication program by conducting an intensive polio immunization program throughout Indonesia through an immunization development program immunization development program/PPI since 1980. The final journey of polio eradication is still challenging and difficult. Since the introduction of the poliovirus vaccine in the 1950s and early 1960s, the effectiveness of the vaccine to prevent poliomyelitis has been clearly demonstrated.